The effects of three consecutive 12-hour shifts on cognition, sleepiness, and domains of nursing performance in day and night shift nurses: A quasi-experimental study. (November 2021) - James, Lois; Elkins-Brown, Nathaniel; Wilson, Marian; James, Stephen M.; Dotson, Elizabeth; Edwards, Charles D.; Wintersteen-Arleth, Laura; Stevens, Kevin; Butterfield, Patricia
Abstract: Background: Healthcare systems have widely adopted consecutive 12 h day and night shifts for nurses, but the effects of these shifts on cognition, sleepiness, and nursing performance remains understudied. Objective: To determine the extent of changes in cognition and sleepiness in nurses working three consecutive 12 h shifts, quantify the respective impacts of these changes on different aspects of nursing performance, and investigate individual differences in all measures. Design: A quasi-experimental, between-within design collected data from nurses between November 2018 and March 2020. The between-groups component was comprised of day shift nurses vs. night shift nurses, while the within-groups component was comprised of two separate test sessions for each nurse: one immediately following a third consecutive shift (fatigued) and one after three consecutive days off work (rested). Setting: Participants were tested in a northwestern US university's nursing simulation laboratory. Participants: A volunteer sample of 94 registered nurses involved in direct patient care working 12 h shifts were recruited from two local hospitals. Methods: Simulated nursing performance was measured in seven separate domains and an aggregate score from the Creighton Competence and Evaluation Inventory, covering both lower- and higher-level constructs like procedural skills, assessment, decision-making, etc. Cognition and sleepiness were assessed through measures of sustained attention, predicted cognitive effectiveness, and subjective sleepiness. Results: In our 94 nurses, individual differences in all our measures varied from trivial to extensive. For six domains of performance and the aggregate score there were no significant differences in means across groups or conditions. For the seventh, Communication skills were lower for night nurses than day nurses, but this effect was small. After three consecutive shifts, sustained attention and predicted cognitive effectiveness decreased, and subjective sleepiness increased. Predicted cognitive effectiveness was particularly low for fatigued night nurses relative to other conditions and was positively correlated with Communication while controlling for other predictors. Conclusions and Relevance: Nurses maintained their levels of performance for all domains after three consecutive shifts. Individual differences in predicted cognitive effectiveness could account for variation in performance by shift type for Communication skills but for no other domain of performance. Communication skills and predicted cognitive effectiveness may interest researchers in the development of fatigue-mitigation strategies for night nurses, but our findings also suggest that more sensitive measures of performance may be necessary to capture other meaningful effects of long, consecutive shifts—if any—on patient care. Tweetable abstract: The effects of three consecutive 12 h shifts on cognition, sleepiness, and domains of nursing performance in day and night shift nurses: A quasi-experimental study.